Usability Assessment of a Waste Bank Customer Management Application Using the System Usability Scale (SUS) - Malahayati, Malahayati; Nadeak, Ebtaria; Sadariawati, Rika (Information Technology and Science (ITScience), 2025)
Waste Bank is a participatory solution for community-based waste management that provides positive economic and environmental impacts. At a waste bank, community members can deposit separated waste such as plastic, paper, cans, and bottles, as savings. The waste is weighed and assessed based on its type, then its value is converted into savings, similar to a conventional bank. To support the development of waste banks, effective and efficient management of customer data is essential, which can be facilitated through digital applications. This waste bank management application streamlines administrative processes, transaction tracking, and data management related to waste collection activities. The application offers several core features to support data recording and management activities, including customer data management, waste deposit logging, transaction tracking, and waste collection driver coordination. This study aims to evaluate the usability level of the prototype of the Bank Sampah Sakur Palembang customer data management application using the System Usability Scale (SUS) method. The evaluation was conducted with ten respondents who are potential users, consisting of administrative staff and customers. The analysis results show that the prototype received a SUS score of 87, which falls into the excellent and acceptable categories. These findings indicate that the application has a high-quality user interface, is easy to use, and has strong potential for further implementation to support the digital operations of waste bank. These results highlight the application's potential for supporting digital transformation in community-based environmental management systems